Targeting risk factors for type 2 diabetes in American Indian youth: the Tribal Turning Point pilot study. Issue 5 (21st June 2017) - Sauder, K. A.; Dabelea, D.; Bailey‐Callahan, R.; Kanott Lambert, S.; Powell, J.; James, R.; Percy, C.; Jenks, B. F.; Testaverde, L.; Thomas, J. M.; Barber, R.; Smiley, J.; et al.
Summary: Background: American Indian (AI) youth are at high risk for type 2 diabetes. Objectives: To partner with Eastern Band of Cherokee Indians and Navajo Nation to develop a culturally sensitive behavioural intervention for youth (Tribal Turning Point; TTP) and assess feasibility in an 8‐month randomized pilot study. Methods: We enrolled 62 overweight/obese AI children (7–10 years) who participated with ≥1 parent/primary caregiver. Intervention participants ( n = 29) attended 12 group classes and five individual sessions. Control participants ( n = 33) attended three health and safety group sessions. We analysed group differences for changes in anthropometrics (BMI, BMI z ‐score, waist circumference), cardiometabolic (insulin, glucose, blood pressure) and behavioural (physical activity and dietary self‐efficacy) outcomes. Results: Study retention was 97%, and intervention group attendance averaged 84%. We observed significant treatment effects ( p = 0.02) for BMI and BMI z ‐score: BMI increased in control (+1.0 kg m −2, p < 0.001) but not intervention participants (+0.3 kg m −2, p = 0.13); BMI z ‐score decreased in intervention (−0.17, p = 0.004) but not control participants (0.01, p = 0.82). There were no treatment effects for cardiometabolic or behavioural outcomes. Conclusions: We demonstrated that a behavioural intervention is feasible to deliver and improved obesity measures in AI youth. Future work should evaluate TTP for effectiveness, sustainability and long‐term impact in expanded tribal settings.